2004
DOI: 10.1021/tx0340753
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tobacco Blend Additives on the Retention of Nicotine and Solanesol in the Human Respiratory Tract and on Subsequent Plasma Nicotine Concentrations during Cigarette Smoking

Abstract: The influence of the tobacco additives diammonium hydrogen phosphate (DAP) and urea on the delivery and respiratory tract retention of nicotine and solanesol and on the uptake of nicotine into venous blood was investigated in 10 smokers under mouth-hold and 75 and 500 mL inhalation conditions. Three cigarettes with identical physical specifications were produced from a common lamina tobacco blend. The control cigarette contained nonammoniated reconstituted tobacco sheet (RTS), whereas DAP and other ammonia com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 16 publications
5
44
0
2
Order By: Relevance
“…Mullard et al reported the average total retention of solanesol (smoke particulate matter) as 48 ± 8% (Table 16) using an inhalation volume that 15% of the subjects' vital capacity. This inhalation volume of 15% of the subjects' vital capacity equates to a volume of 500-600 ml, so the retention of 48% reported by Mullard et al is lower than the 61% reported by Frost et al and the 66% reported by Armitage et al (2004aArmitage et al ( , 2004b) (see next section). This is likely to be due to differences in the experimental methodology used in the various studies.…”
Section: Studies Using Gravimetric Determination Of Particulate Mattermentioning
confidence: 86%
“…Mullard et al reported the average total retention of solanesol (smoke particulate matter) as 48 ± 8% (Table 16) using an inhalation volume that 15% of the subjects' vital capacity. This inhalation volume of 15% of the subjects' vital capacity equates to a volume of 500-600 ml, so the retention of 48% reported by Mullard et al is lower than the 61% reported by Frost et al and the 66% reported by Armitage et al (2004aArmitage et al ( , 2004b) (see next section). This is likely to be due to differences in the experimental methodology used in the various studies.…”
Section: Studies Using Gravimetric Determination Of Particulate Mattermentioning
confidence: 86%
“…Nicotine, the main component of tobacco, is a natural alkaloid. The average nicotine amount per cigarette ranges from 1 to 1.8 mg, and saliva concentrations could reach 115 ng/ml, as measured by gas-liquid chromatography [3,4]. Nicotine-induced pathological changes in human periodontal tissue alter the morphology and structure of cells, decrease bone volume and cause loss of teeth [1,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, after hitting the lung surface nicotine always exists in a 20:80 ratio of un-protonated:mono-protonated nicotine regardless of the form it enters the lungs. A small study by ARMITAGE et al (131) showed in 2004 that the treatment of cigarette tobacco with urea or diammonium hydrogen phosphate failed to increase the venous blood levels of nicotine in smokers compared to additive free control cigarettes. The study investigated the delivery and respiratory tract retention of nicotine and solanesol from cigarettes containing urea or diammonium hydrogen phosphate in ten smokers under the conditions of mouth-holding and inhaling volumes of 75 mL and 500 mL.…”
Section: Tobacco Additives Like Ammonium Compounds That Are Alleged Tmentioning
confidence: 99%